Investigating Structural, Mechanical, Electronic and Magnetic Properties of Spin-Gapless Quaternary Heusler Alloy CrMnVAl - Ray, R. B.; Rai, R. K.; Kaphle, G. C. (Pragya Darshan प्रज्ञा दर्शन, 2024)
Utilizing density functional theory (DFT), the study thoroughly investigates the equiatomic quaternary Heusler compound CrMnVAl, revealing its promising properties across multiple domains. The energy minimization curve shows its structural stability with lattice parameter 5.91Å in ferromagnetic phase. The negative values of formation and cohesive energy indicate its chemical stability, while electronic structure analysis demonstrates spin gapless semiconducting behavior. The total spin magnetic moment of this compound is almost 3.00 μB obeying the Slater-Pauling 18 electron rule (Mt = Zt – 18). The 100% spin polarisation and the Curie temperature higher than ambient temperature indicate that this compound acts as a promising material for spin dependent applications. Furthermore, exploring its mechanical properties complements these findings, offering insights into its structural integrity and suitability for diverse applications. Overall, the study underscores CrMnVAl's potential as a versatile material for spintronics and beyond.